Biomechanical characterization of cartilages by a novel approach of blunt impact testing - Varga, Ferdinand; Držík, Milan; Handl, Milan; Chlpík, Juraj; Kos, Petr; Filová, Eva; Rampichová, Michala; Nečas, Alois; Trč, Tomáš; Amler, Evžen (Physiological research, 2007)
The present article introduces a novel method of characterizing the macromechanical cartilage properties based on dynamic testing. The proposed approach of instrumented impact testing shows the possibility of more detailed investigation of the acting dynamic forces and corresponding deformations within the wide range of strain rates and loads, including the unloading part of stress-strain curves and hysteresis loops. The presented results of the unconfined compression testing of both the native joint cartilage tissues and potential substitute materials outlined the opportunity to measure the dissipation energy and thus to identify the initial mechanical deterioration symptoms and to introduce a better definition of material damage. Based on the analysis of measured specimen deformation, the intact and pathologically changed cartilage tissue can be distinguished and the differences revealed.
Keywords: Stress, Mechanical; testování materiálů; Tissue Engineering; Cells, Cultured; Humans; pružnost; Cartilage, Articular; zvířata; Prosthesis Failure; Models, Biological; tkáňové inženýrství; Elasticity; Time Factors; mechanický stres; biologické modely; chondrocyty; Tissue Scaffolds; selhání protézy; časové faktory; kultivované buňky; pevnost v tlaku; tkáňové podpůrné struktury; Animals; Compressive Strength; lidé; Materials Testing; kloubní chrupavka; Chondrocytes